Mechanisms of in-plane shear deformation in hybrid three-dimensional woven composites. (December 2015) - Muñoz, R; González, C; Llorca, J
The in-plane shear response of a hybrid three-dimensional woven composite laminate is studied, and the deformation and failure micromechanisms are analysed by means of full-field strain measurements and X-ray microtomography. It was found that the laminate presented a very high failure strain ( ≈38%), much higher than that of conventional two-dimensional laminates. Extensive damage was clearly observed during deformation in the form of matrix/fibre debonding and tow splitting by shear. Nevertheless, the through-thickness reinforcement hindered the development of failure by interply delamination and improved the ductility. Final fracture took place by tensile fibre failure, and the strain-to-failure was enhanced by the higher ductility of the glass fibres.